Ezequiel Rojas: Between Utilitarianism and Ideology - Hurtado, Jimena (2015)
Political economy played a central role in the construction of the new Republic of Colombia through the influence of Ezequiel Rojas. In his pursuit of theoretical and practical guidance to organize a new society of free individuals pledged to happiness, Rojas looked to political economy for inspiration. However, the sources that Rojas drew on did not belong to the tradition of classical political economy; he based his own approach on other, less traditional sources; namely utilitarianism and ideology. In this text I aim to reconstruct this approach, showing its tensions and contradictions and the way in which Rojas tried to address them through religion.